Genomic evidence of introgression and adaptation in a model subtropical tree species, Eucalyptus grandis. Issue 3 (14th September 2020) - Mostert‐O'Neill, Marja Mirjam; Reynolds, Sharon Melissa; Acosta, Juan Jose; Lee, David John; Borevitz, Justin O.; Myburg, Alexander Andrew
Abstract: The genetic consequences of adaptation to changing environments can be deciphered using population genomics, which may help predict species' responses to global climate change. Towards this, we used genome‐wide SNP marker analysis to determine population structure and patterns of genetic differentiation in terms of neutral and adaptive genetic variation in the natural range of Eucalyptus grandis, a widely cultivated subtropical and temperate species, serving as genomic reference for the genus. We analysed introgression patterns at subchromosomal resolution using a modified ancestry mapping approach and identified provenances with extensive interspecific introgression in response to increased aridity. Furthermore, we describe potentially adaptive genetic variation as explained by environment‐associated SNP markers, which also led to the discovery of what is likely a large structural variant. Finally, we show that genes linked to these markers are enriched for biotic and abiotic stress responses.